A reassessment of the relationship between aroK- and aroL-encoded shikimate kinase enzymes of Escherichia coli. - Whipp, M J (1995)
In the course of sequencing the aroK gene, a number of errors were found in the published sequence. The corrected sequence alters the length of the aroK coding region such that the AroK and AroL proteins are now of comparable length and the homology between them extends the entire length of the two enzymes.